Mamãe é a melhor professora!: uma etnografia junto a três famílias que educam suas crianças fora da escola - Loreti, Gabriela Braga (2019)
This ethnography was developed among three families that educated their children out of school. The term education out of the school is used here in its broader form to refer to those situations when grown-ups, either parents or legal responsibles, choose to take direct responsability over their children’s education, avoiding sending them to the educational system, either public or private. Among those practices, there are those known in Brazil as educação domiciliar or não escolarização or homeschooling and unschooling. At the time in which this research was being developed, its controversial legal status was at evidence, being them not regulated, and, at the same time, there was a increase on the number of practitioners or interested families. Thereby, the choice of having the children not attending the school and being therefore educated at home is the conducting wire of this work, that turns to the experiences among the three families, who are seen by their similarities or dissimilarities, to reflect about ideas of family, education, care and children involved in each case. We intend to make this experiences explicit from the displacements proposed by these women, mothers and educators, from the formal education, who explained to me what, for them, is to educated their children out of school as well as, at the same time, how they organized and conducted meals, play times, researches and activities, accompanying those families at home as well as their everyday itinerary when leaving their homes.